Trauma-Induced Coagulopathy - Petros, Sirak (Hämostaseologie, 2019)
Trauma-induced coagulopathy (TIC) is a heterogeneous entity that contributes to a significant morbidity and mortality following trauma. The activated protein C system, endotheliopathy and platelet dysfunction have been implicated in the pathogenesis of TIC, although there are still controversies on the exact pathogenesis. TIC can be modified by hypoperfusion, acidosis, hypothermia, haemodilution, underlying disease conditions, pre-injury medications as well as genetic predispositions. Current definition of this syndrome is based on laboratory abnormalities that do not easily allow a distinction between adaptive and maladaptive changes of the haemostatic system. The management of the coagulopathy in the early phase of trauma focuses on the treatment of bleeding. The improving quality in the early damage control following trauma has led to a marked reduction in morbidity and mortality. In the later phase, hypercoagulopathy and inflammation contribute to organ dysfunction, venous thromboembolism and poor outcome. Despite considerable advances in trauma management, TIC remains a diagnostic and therapeutic challenge both in the early and late phases of trauma. This review mainly focuses on the pathogenesis of TIC, with a very short discussion on diagnostic and therapeutic principles.
Keywords: trauma; coagulopathy; trauma-induced coagulopathy; bleeding